Business Continuity Management For Data Outage Disruptor: A Study On A Private Hospital In Negeri Sembilan - Noorfarhah Mohd Haris; Rabihah Md Sum (Asian Scholars Network (ASNet), 2024)
International Journal of Business and Technology Management Vol. 5, No. 4 Page (37-43)